METHODS FOR THE DEVELOPMENT OF TOURISM VIA THE INTERNET - Abdurashidova, Nilufar (Журнал иностранных языков и лингвистики, 2023)
Our article is devoted to one of the trends in the development of tourism, in particular its work in the Internet space. The purpose of this article is to identify the features of the tourist vocabulary of the modern Uzbek language under the influence of Internet speech.